Educational features of Malaysian robot contest - Shafie, Amir Akramin; Baharum, Zalinda (Springer -Verlag, 2004)
The educational experiences from robot contest of entry, junior and advance level are presented based on guided constructionism approach in education that combines hands on guidance with hands-on experience. The aim of the competition as a whole are to allow the student to (i) conceptualise the robot (ii) manage the non-deterministic characteristic of the environment and (iii)manage integrated hardware and software development projects. Indeed with this knowledge the student should be able to win a number of international robot tournaments.